THE EFFECT OF PERFORMANCE EXPECTATIONS, EFFORT EXPECTATIONS, FACILITATING CONDITIONS AND SOCIAL INFLUENCE ON BEHAVIOR INTENTION TO PAY ZAKAT THROUGH THE QRIS DIGITAL PLATFORM IN BAITUL MAL ACEH - Rahmawati, Mujiyani; Nurdin, Ridwan (Universitas Syiah Kuala, 2024)
This study aims to determine the effect of performance expectations, business expectations, facilitating conditions and social influences on the behavioral intention to pay zakat through the QRIS digital platform at Baitul Mal Aceh. The sample used in the study was 100 respondents selected using the Slovin formula and using Non-Probability Sampling with the Purposive Sampling method. The methodology used is quantitative with the Multiple Linear Regression approach. The results of the study partially show that the performance expectation variable has a positive and significant effect on the behavioral intention to pay zakat through the QRIS digital platform, and business expectations have a negative and significant effect on the behavioral intention to pay zakat through the QRIS digital platform. While the facilitating conditions and social influences do not affect the behavioral intention to pay zakat through the QRIS digital platform. While simultaneously (together) the performance expectation variable, business expectations, facilitating conditions, and social influences have a effect on the behavioral intention to pay zakat through the QRIS digital platform.Keywords: Performance Expectation, Effort Expectation, Facilitating Conditions, Social Influence, Behavior Intention, QRIS, Zakat